Validity and Reliability of the Turkish Version of the Prosthesis Donning and Doffing Questionnaire for Persons with Transtibial Amputations - GÜNDÜZ, OSMAN HAKAN (My University, 2022)
Introduction: Satisfaction with the donning and doffing procedure of prosthesis is related to the quality of life of individuals with amputation, and it should be assessed to gather information about related challenges, thus forming the basis for possible solutions. This study aimed to investigate the construct validity and reliability of the Turkish version of the Prosthesis Donning and Doffing Questionnaire for individuals with transtibial amputation. Materials and Methods: After a translation/retranslation process, 30 individuals with transtibial amputation were recruited to evaluate the validity and reliability of the questionnaire. The participants were asked to fill in the Turkish version of the Prosthesis Donning and Doffing Questionnaire, Satisfaction with Prosthesis Survey, and the Nottingham Health Profile. The Prosthesis Donning and Doffing Questionnaire was readministered after 3 days. Results: Test-retest reliability showed good intraclass correlation coefficient (ICC, 0.739; 95% confidence interval, 0.46–0.87). There was a statistically significant correlation between the Prosthesis Donning and Doffing Questionnaire, the Satisfaction with the Prosthesis Survey (rho = 0.419, P = 0.02), and Nottingham Health Profile (rho = −0.656, P = 0.0001), and its subsets (P < 0.05) showed construct validity. Conclusions: The Turkish version of the Prosthesis Donning and Doffing Questionnaire is a reliable and valid tool to assess donning and doffing of prostheses for individuals with transtibial amputation. (J Prosthet Orthot. 2022;34:122–130)
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; ORTOPEDİ; Klinik Tıp; Klinik Tıp (MED); REHABİLİTASYON; ORTHOPEDICS; CLINICAL MEDICINE; Clinical Medicine (MED); REHABILITATION; Ayak Bakımı; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Ortopedi ve Spor Hekimliği; Podiatry; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation; Orthopedics and Sports Medicine; amputation; prosthesis; Prosthesis Donning and Doffing Questionnaire; psychometrics; rehabilitation; satisfaction; validation; QUALITY-OF-LIFE; PATIENT; SATISFACTION; TRANSLATION; EXPERIENCE; OUTCOMES; amputation; prosthesis; Prosthesis Donning and Doffing Questionnaire; psychometrics; rehabilitation; satisfaction; validation